Leader and the Leadership of the Prophet Muhammad: Strategy and Innovation in the Battle of Trench - Afifi, Abdullah A (IDRIS Darulfunun Institute, 2024)
This article examines Prophet Muhammad's strategic and innovative leadership during the Battle of the Trench, a pivotal event in early Islamic history. Faced with a large confederate army, Muhammad adopted the unprecedented strategy of digging a trench around Medina, demonstrating his adaptability and inclusiveness by accepting a Persian companion's suggestion, Salman al-Farsi. This tactic effectively neutralized the enemy's advantage, highlighting Muhammad’s foresight and strategic acumen which can only be seen if we read the references in detail and feel the tense occurred on that day. The analysis of this article focuses on Muhammad's leadership qualities, including visionary strategy, resilience, ethical conduct, and inspirational influence. These attributes were crucial in uniting and motivating the Muslim community under extreme adversity. The successful defence of Medina not only solidified the Muslim community but also set new precedents in military tactics and ethical warfare, influencing Islamic governance and leadership principles. The Battle of the Trench serves as a significant historical case study of strategic and ethical leadership shown by Muhammad in facing a direct enemy from outside and a potential internal enemy that turns up in that despairing situation. The insights drawn from Muhammad’s leadership approach are relevant to modern leadership and contemporary challenges, transcending religious and cultural contexts. This article contributes to the discourse on leadership, strategy, and crisis management, underscoring the enduring relevance of Muhammad's leadership principles which have proven effective in saving the situation.